Combining SERS and microspectrofluorimetry with historically accurate reconstructions for the characterization of lac dye paints in medieval manuscript illuminations - Castro, Rita; Pozzi, Federica; Leona, Marco; Melo, Maria Joao (Journal of Raman Spectroscopy, 2014)
n/a
Melo, Maria Joao/C-8594-2011 Melo, Maria Joao/0000-0001-7393-6801 Si 1